STRATEGI BISNIS DENGAN LIFE CYCLE INDUSTRI DAN PERUSAHAAN - RGatot Heru Pranjoto (Kompetensi (Competence : Journal of Management Studies), 2015)
Strategic financial planning vary according to the stages of the business cycle, where the business cycle consists of four stages, where financial strategy planning, arranged on the business cycle, requires the role of finance director who acted as a financial expert or financial architecture which serves to prepare the company's financial fundamentals. Improved fundamental values that are in line with the increase in the value of the company can be achieved when supported by the appropriate financial strategy, which includes investment decisions and how the provision of financial resources.A failure to analyze the company's position, it can be fatal, because each stage of the business cycle requires a source and a different funding, over or lack of operational funds may result in less smooth operations of the company, which in turn result in failure to achieve the company's goal to make a profit in the short term and in the run length should be achieved return on equity and the value of the company.Companies that are growing rapidly, requiring large funds, the business strategy with the merged horizontally as a solution, because it can help synergy financially through reduced cost of capital, or more robust capital structure by increasing the assets after the merger, while the company reached a stage of maturity, the business strategy with a horizontal merger, in order to reduce competition, positive contribution can occur, if, after the merger synergy financial, managerial, production and marketing, production Synergy for example, the company is able to achieve economies of scale and cost of capital efficiency